Left renal agenesis with left ectopic ureter opening into vas deferens with urinary tract infection: Managed conservatively - A rare case report (Indian Journal of Case Reports, 2020)
Renal agenesis with an ectopic ureter draining into the reproductive system is a rare entity. It usually presents before third decade of life. We are reporting a case of delayed presentation of left renal agenesis with ectopic ureter opening into the vas deferens without infertility presenting due to urinary tract infection and managed conservatively.